East India company career of Sir Robert Cowen in Bombay and the western Indian ocean, C. 1719-35. - TEGGIN, EDWARD OWEN (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2020)
This thesis explores the life and career of Sir Robert Cowan, governor of Bombay 1729-34. The broad date range stretches from 1680 to 1750, whilst the primary focus has been on the period 1719-35. This reflects Cowan's Indian career across the settlements of Goa, Surat, Mocha and Bombay. This research draws from the considerable archive of Cowan's personal correspondence and accounts held at PRONI, Belfast. These have been compared and contrasted with East India Company material from the India Office Records held at the British Library, London, together with sources from the National Archives, Kew. This thesis has aimed to construct a study of Cowan's career, whilst engaging with the central research topic of expanding on Company history in the western Indian Ocean through the lens of Cowan's archive. This has been done to enable a more focused approach to his career and the wider Company history, and was felt to be the most effective method available. Through its investigation into Cowan, this thesis builds on the existing understandings of East India Company operations in the western Indian Ocean during the early eighteenth century. This incorporates Cowan's impact on trade, security, interaction with native elites, Company politics and interpersonal networks. The opportunity of incorporating the large personal archive of Cowan into the existing evaluation of intra-Asian commerce has allowed for further investigation into the global networks which linked commerce in the mercantilist age. As such, this thesis builds upon the recent trend in scholarship towards global perspectives of history.
APPROVED
Keywords: East India Company; Mercantile Networks; Indian Ocean; Bombay; Private Trade